Investigation on the Negative Capacitance Field Effect Transistor with Dual Ferroelectric Region - Jia-Fei Yao; Xue Han; Xin-Peng Zhang; Jin-Cheng Liu; Ming-Yuan Gu; Mao-Lin Zhang; Ke-Han Yu; Yu-Feng Guo (Crystals, 2022)
This paper proposes a new structure of the negative capacitance field effect transistor (NCFET), which features of the dual ferroelectric region (DFR) when compared to the conventional NCFET. The dual ferroelectric region with FE1 region and FE2 region forms a non-uniform voltage amplification effect, leads to the significantly improvement of the gate control ability and modulates the electric characteristics of the NCFET. The mechanism of the voltage amplification effect, polarization reversal, channel surface electric field, and ferroelectric polarization intensity distributions are investigated. The influences of the ferroelectric parameters α and β on the electric characteristics are discussed. The results show that the DFR-NCFET is able to obtain a subthreshold swing (SS) below the Boltzmann limit (60 mV/dec) by increasing the ferroelectric parameter α of the FE2 region.